Non-invasive imaging of tau-targeted probe uptake by whole brain multi-spectral optoacoustic tomography. - Vagenknecht, Patrick; Luzgin, Artur; Ono, Maiko; Ji, Bin; Higuchi, Makoto; Noain, Daniela; Maschio, Cinzia A.; Sobek, Jens; Chen, Zhenyue; Konietzko, Uwe; Gerez, Juan A.; Riek, Roland; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2022)
Purpose: Abnormal tau accumulation within the brain plays an important role in tauopathies such as Alzheimer's disease and frontotemporal dementia. High-resolution imaging of tau deposits at the whole-brain scale in animal disease models is highly desired. Methods: We approached this challenge by non-invasively imaging the brains of P301L mice of 4-repeat tau with concurrent volumetric multi-spectral optoacoustic tomography (vMSOT) at ~ 115 μm spatial resolution using the tau-targeted pyridinyl-butadienyl-benzothiazole derivative PBB5 (i.v.). In vitro probe characterization, concurrent vMSOT and epi-fluorescence imaging of in vivo PBB5 targeting (i.v.) was performed in P301L and wild-type mice, followed by ex vivo validation using AT-8 antibody for phosphorylated tau. Results: PBB5 showed specific binding to recombinant K18 tau fibrils by fluorescence assay, to post-mortem Alzheimer's disease brain tissue homogenate by competitive binding against [11C]PBB3 and to tau deposits (AT-8 positive) in post-mortem corticobasal degeneration and progressive supranuclear palsy brains. Dose-dependent optoacoustic and fluorescence signal intensities were observed in the mouse brains following i.v. administration of different concentrations of PBB5. In vivo vMSOT brain imaging of P301L mice showed higher retention of PBB5 in the tau-laden cortex and hippocampus compared to wild-type mice, as confirmed by ex vivo vMSOT, epi-fluorescence, multiphoton microscopy, and immunofluorescence staining. Conclusions: We demonstrated non-invasive whole-brain imaging of tau in P301L mice with vMSOT system using PBB5 at a previously unachieved ~ 115 μm spatial resolution. This platform provides a new tool to study tau spreading and clearance in a tauopathy mouse model, foreseeable in monitoring tau targeting putative therapeutics.